Energy Saving at Cities - Manzano Agugliaro, Francisco; Perea Moreno, Alberto Jesús (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Climate change is increasing due to the anthropogenic emission of greenhouse gases. The majority of these are due to the production and consumption of energy. According to the latest estimates, global energy demand could triple by 2050, and by then, 70% of the world's population will live in cities. The challenge for future cities is the implementation of a mechanism that minimizes the need for injection of new energy resources in them, so that a high level of self-sufficiency can be achieved through the concept of circular economy, thus partially mitigating the impacts of climate change. Using solar energy today is considered to be one of the best solutions that can be installed in buildings to help with this issue. This book addresses several relevant aspects related to energy saving at cities, including a deep survey of research topics and scientific collaborations in energy saving. The main research topics carried out are related to sustainability, solar energy, the use of rooftops for energy generation, energy conversion from urban biomass or residues, wind energy, and public and private urban energy saving.